Epidemiology of serogroup C and Y invasive meningococcal disease (IMD) in Ontario, 2000–2013: Vaccine program impact assessment. Issue 42 (13th October 2015) - Wormsbecker, A.E.; Wong, K.; Jamieson, F.B.; Crowcroft, N.S.; Deeks, S.L.
Abstract Objectives A publicly-funded meningococcal serogroup C conjugate vaccine (MCCV) program was introduced in Ontario, in 2004/2005 for 1-year-old children as well as adolescents (approximately 12 years old). In 2009, quadrivalent meningococcal conjugate vaccine (MCV4) replaced MCCV for grade seven students. Our objective was to determine meningococcal vaccine program impact on reported cases of serogroup C and Y invasive meningococcal disease (IMD) at the population level in Ontario, Canada. Methods Data were obtained from the Ontario reportable diseases system, the integrated Public Health Information System (iPHIS), and Public Health Ontario Laboratories (PHOL) for 2000–2013. Descriptive epidemiologic analyses, including age-specific rates for age groups based on program eligibility, were conducted. Changes over the 14-year observation period and comparison of pre- and post-program periods for MCCV and MCV4 were assessed. Analyses were conducted using SAS 9.3. Results There were 161 serogroup C IMD cases and its annual incidence decreased significantly over time (17.2% reduction per year [95% CI: 13.4 to 20.7]). The incidence of serogroup C IMD decreased significantly in children aged 1–17 years in the post-program period, based on age-specific incidence rate ratios (IRRs) and their 95% confidence intervals (CIs). Adolescents 12–16 years had the lowest serogroup C IRR (0.07 [95% CI: 0.01 to 0.55]); the rate decreased more than 14-fold between the pre- and post-periods. There were 187 serogroup Y IMD cases and there was a non-significant 1.6% reduction per year [95% CI: −1.9 to 5.1]) over the surveillance period. Likewise, there was a non-significant decrease in serogroup Y IMD among persons 12–16 years (MCV4 eligible) in the post-program period. Conclusions Reductions in serogroup C IMD among program eligible and ineligible age groups suggest both direct and indirect MCCV vaccine program impact. Continued surveillance of IMD in Ontario is important to further assess MCV4 program impact.